Changing the Receptor Specificity of Anthrax Toxin - Adva Mechaly (American Society for Microbiology, 2012)
ABSTRACT The actions of many bacterial toxins depend on their ability to bind to one or more cell-surface receptors. Anthrax toxin acts by a sequence of events that begins when the protective-antigen (PA) moiety of the toxin binds to either one of two cell-surface proteins, ANTXR1 and ANTXR2, and is proteolytically activated. The activated PA self-associates to form oligomeric pore precursors, which, in turn, bind the enzymatic moieties of the toxin and transport them to the cytosol. We introduced a double mutation into domain 4 of PA to ablate its native receptor-binding function and fused epidermal growth factor (EGF) to the C terminus of the mutated protein. The resulting fusion protein transported enzymatic effector proteins into a cell line that expressed the EGF receptor (A431 cells), but not into a line lacking this receptor (CHO-K1 cells). Addition of excess free EGF blocked transport of effector proteins into A431 cells via the fusion protein, but not via native PA. We also showed that fusing the diphtheria toxin receptor-binding domain to the C terminus of the mutated PA channeled effector-protein transport through the diphtheria toxin receptor. PA fusion proteins with altered receptor specificity may be useful in biological research and could have practical applications, including ablation or perturbation of selected populations of cells in vivo. IMPORTANCE Bacterial toxins that act within mammalian cells have receptor-dependent mechanisms to transport their enzymatic components to the cytoplasmic compartment. By inactivating or otherwise modifying their respective intracellular targets, these intracellular effectors disrupt metabolic pathways and in some cases cause death of the cell. Our results show that the receptor specificity of the transport protein of anthrax toxin may be readily changed, raising the possibility that receptor-redirected forms of protective antigen (PA) and PA homologs may be useful for research and medical applications requiring modification or ablation of designated populations of cells.